Parental obesity-induced changes in developmental programming - Cechinel, Laura R.; Batabyal, Rachael A.; Freishtat, Robert J.; Zohn, Irene E. (Frontiers in Cell and Developmental Biology, 2022)
Many studies support the link between parental obesity and the predisposition to develop adult-onset metabolic syndromes that include obesity, high blood pressure, dyslipidemia, insulin resistance, and diabetes in the offspring. As the prevalence of obesity increases in persons of childbearing age, so does metabolic syndrome in their descendants. Understanding how parental obesity alters metabolic programs in the progeny, predisposing them to adult-onset metabolic syndrome, is key to breaking this cycle. This review explores the basis for altered metabolism of offspring exposed to overnutrition by focusing on critical developmental processes influenced by parental obesity. We draw from human and animal model studies, highlighting the adaptations in metabolism that occur during normal pregnancy that become maladaptive with obesity. We describe essential phases of development impacted by parental obesity that contribute to long-term alterations in metabolism in the offspring. These encompass gamete formation, placentation, adipogenesis, pancreas development, and development of brain appetite control circuits. Parental obesity alters the developmental programming of these organs in part by inducing epigenetic changes with long-term consequences on metabolism. While exposure to parental obesity during any of these phases is sufficient to alter long-term metabolism, offspring often experience multiple exposures throughout their development. These insults accumulate to increase further the susceptibility of the offspring to the obesogenic environments of modern society.